Contrarracionalidade no centro de Campinas: a (sobre)vivência dos trabalhadores da alimentação frente à imposição do planejamento estratégico - Livia Cangiano Antipon (Confins)
The center of Campinas, which hosts a dense mass food circuit, plays an important role for the poor inhabitants: there their economies can be established, which guarantees the survival of this part of the city's workers. Based on a bibliographical review and information collected in field work, we approach both the links between the revitalization project of Avenida Francisco Glicério and the daily trajectories of the various subjects that make up this circuit, as well as the countless ways of survival in the unequal metropolis. It is a matter of looking at the problematic substantiated by the clash between the strategic planning imposed on the places and the response of these places and their subjects, combining alternatives and resisting the deterioration of the ways of living and surviving in the city. The analysis of the popular food market spaces proved to be a vital element for the reflection of the urban crisis in Campinas, highlighting the presence of the hidden hunger in the city and the counter-rational gestures of the poor social subjects who organize their own economic spaces.